Allele-Specific Interactions between CAST AWAY and NEVERSHED Control Abscission in Arabidopsis Flowers - Groner, William D.; Christy, Megan E.; Kreiner, Catherine M.; Liljegren, Sarah J. (Frontiers in Plant Science, 2016)
An advantage of analyzing abscission in genetically tractable model plants is the ability to make use of classic genetic tools such as suppression analysis. We have investigated the regulation of organ abscission by carrying out suppression analysis in Arabidopsis flowers. Plants carrying mutations in the NEVERSHED (NEV) gene, which encodes an ADP-ribosylation factor GTPase-activating protein, retain their outer floral organs after fertilization. Mutant alleles of CAST AWAY (CST), which encodes a receptor-like cytoplasmic kinase, were found to restore organ abscission in nev flowers in an allele-specific manner. To further explore the basis of the interactions between CST and NEV, we tested whether the site of a nev mutation is predictive of its ability to be suppressed. Our results suggest instead that the strength of a nev allele influences whether organ abscission can be rescued by a specific allele of CST.